Arrival of Austronesian Immigrants in the Java Sea Region, Central Java, Indonesia: A New Dating Interpretation - Sulistyarto, Priyatno Hadi; Kasnowihardjo, Gunadi; Rahayuningsih, Restu A. (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2024)
The research analyzes the chronology of the arrival of Austronesian speakers in the Java Sea Region, Indonesia, through absolute and relative dating analysis. Radiocarbon dating analysis of findings of human skeletons from research at the Leran and Plawangan Sites, Central Java Province, and the East Tamberu Site, East Java Province, shows significant dating, namely, far past historical times. Relative dating analysis is based on textual and artifactual data found contextually on Bawean Island in the Java Sea Region. The discovery of absolute and relative dating results can fill in the gaps in the chronology of the arrival of the Austronesian speakers in the Java Sea Region, the North Coast of Java, and the Madura Islands. Bawean Island is thought to be a transit area for Austronesian speakers, so absolute dating samples were taken from the closest and farthest sites from Bawean Island, namely Leran and Tamberu Timur sites. Meanwhile, 2 Long Grave Units were found on Bawean Island as relative dating samples. Both will provide information on the chronology of the arrival of Austronesian speakers in the Java Sea area.